Haptic Nudging Using a Wearable Device to Promote Upper Limb Activity During Stroke Rehabilitation: Exploring Diurnal Variation, Repetition, and Duration of Effect - Signal, Nada; Olsen, Sharon; Rashid, Usman; McLaren, Ruth; Vandal, Alain; King, Marcus; Taylor, Denise (MDPI AG, 2023)
Haptic nudging via wearable devices promotes physical activity and may increase upper limb movement in stroke rehabilitation. This study investigated the optimal approach to haptic nudging by examining diurnal variation, duration of effect, and repeated nudging. The study analysed data from a multiple-period randomised crossover study. A 12 h inpatient rehabilitation day was divided into 72 intervals in which participants with stroke (n = 20) randomly received either a ‘nudge’ or ‘no nudge’. Upper limb movement was observed, classified, and analysed using longitudinal mixed models. The odds of affected upper limb movement following a nudge compared with no nudge were significantly higher during active periods such as breakfast, lunch, and morning and afternoon activities (odds ratios (ORs) 2.01–4.63, 95% CIs [1.27–2.67, 3.17–8.01]), but not dinner (OR 1.36, 95% CI [0.86, 2.16]). The effect of nudging was no longer statistically significant at 50–60 s post-nudge. Consecutive delays in nudging significantly decreased the odds of moving when a nudge was eventually delivered. Contrary to expectations, people with stroke appear more responsive to haptic nudging during active periods rather than periods of inactivity. By understanding the optimal timing and frequency of haptic nudging, the design of wearable devices can be optimised to maximise their therapeutic benefits.
Keywords: 1701 Psychology; 1702 Cognitive Sciences; 3202 Clinical sciences; 5202 Biological psychology; 5203 Clinical and health psychology